Analisis kadar feritin sebagai prediktor risiko Intrauterine Growth Restriction (IUGR) pada ibu hamil Komunitas Suku Anak Dalam di Kabupaten Tebo Jambi - Fitri, Samnil Astuti; Agustina, Fitratur Rahmah; Ali, Jumaidi (Poltekkes Kemenkes Aceh, 2025)
Background: Intrauterine Growth Restriction (IUGR) is one of the leading causes of perinatal morbidity and mortality, particularly among vulnerable populations. Ferritin reflects iron storage and has the potential to serve as a predictive biomarker for IUGR, while socio-cultural factors influence maternal nutritional status and antenatal health behaviors.Objectives: This study aimed to analyze the relationship between ferritin levels and IUGR among pregnant women in the Suku Anak Dalam (SAD) community, and to explore the socio-cultural context that affects iron status and fetal growth.Methods: A mixed-methods study was conducted from July to August 2025 among 31 pregnant women from the Suku Anak Dalam (SAD) community in Tebo Regency, Jambi. Quantitative data were obtained through ferritin measurement using a Ferritin Rapid Test from capillary blood, while IUGR was identified based on fundal height, abdominal girth, and fetal heart rate. Qualitative data were collected through in-depth interviews and observations focusing on dietary practices, cultural beliefs, and access to health services.Results: Nineteen respondents (61,3%) had low ferritin levels (<15 ng/mL), and eight (25,8%) were categorized as having IUGR. Low ferritin levels were significantly associated with IUGR (p=0,02; OR=5,3; 95% CI: 1,1–24,5). Qualitative findings revealed limited dietary diversity, dependence on forest-based foods, and cultural practices that restricted antenatal care access, which indirectly increased the risk of IUGR.Conclusion: Low ferritin levels were significantly associated with an increased risk of IUGR, and socio-cultural factors exacerbated this condition through their influence on maternal nutrition and health behaviors among SAD pregnant women. Integrating simple ferritin screening with an understanding of the socio-cultural context may serve as an effective strategy for early screening and prevention in remote areas.